Does Biology Drive Child Penalties? Evidence from Biological and Adoptive Families - Henrik Kleven; Camille Landais; Jakob Egholt Soegaard (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
This paper investigates if the impact of children on the labor market trajectories of women relative to men child penalties can be explained by the biological links between mother and child. We estimate child penalties in biological and adoptive families using event studies around the arrival of children and almost forty years of adoption data from Denmark. Long-run child penalties in earnings and its underlying determinants are virtually identical in biological and adoptive families. This implies that biology is not important for child-related gender gaps. Based on additional analyses, we argue that our results speak against the importance of specialization based on comparative advantage more broadly.
Keywords: D63; J13; J16; J22; J31; J71; 330; Gender Wage Gap; Children; Adoption; Denmark